π vs σ-Radical States of One-Electron Oxidized DNA/RNA Bases: A Density Functional Theory Study - Kumar, Anil (2013)
As a result of their inherent planarity, DNA base radicals generated by one electron oxidation/reduction or bond cleavage form π- or σ-radicals. While most DNA base systems form π-radicals there are a number of nucleobase analogs such as one-electron oxidized 6-azauraci1, 6-azacytosine, and 2-thiothymine or one-electron reduced 5-bromouracil that form more reactive σ-radicals. Elucidating the availability of these states within DNA, base radical electronic structure is important to the understanding of the reactivity of DNA base radicals in different environments. In this work, we address this question by the calculation of the relative energies of π- and σ-radical states in DNA/RNA bases and their analogs. We used density functional theory B3LYP/6-31++G** method to optimize the geometries of π- and σ-radicals in C(s) symmetry (i.e., planar) in the gas phase and in solution using the polarized continuum model (PCM). The calculations predict that σ- and π-radical states in one electron oxidized bases of thymine, T(N3-H)(•,) and uracil, U(N3-H)(•) are very close in energy, i.e., the π-radical is only ca. 4 kcal/mol more stable than the σ-radical. For the one electron oxidized radicals of cytosine, C(•+), C(N4-H)(•), adenine, A(•+), A(N6-H)(•), and guanine, G(•+), G(N2-H)(•), G(N1-H)(•) the π-radicals are ca. 16 to 41 kcal/mol more stable than their corresponding σ-radicals. Inclusion of solvent (PCM) is found to stabilize the π- over σ-radical of each of the systems. U(N3-H)(•) with three discrete water molecules in the gas phase, is found to form a three-electron σ bond between N3 atom of uracil and O atom of a water molecule but on inclusion of full solvation and discrete hydration the π-radical remains most stable..